An Intrusion Detection System for the Internet of Things based on a hybrid federated learning model - Zerafa Marwa (My University, 2024)
Abstract In recent years, the rapid expansion of the Internet of Things (IoT) has necessitated robust and adaptive security measures to protect against increasingly sophisticated cyber threats. This dissertation presents a comprehensive analysis of federated learning (FL) approaches for intrusion detection in IoT environments. The focus is on developing a decentralized, privacy- preserving intrusion detection system (IDS) that leverages federated learning frameworks to enhance security without compromising data privacy. Various deep learning models, including Convolutional Neural Networks (CNNs),Deep Neural Networks (DNNs) and Long Short-Term Memory (LSTM) networks, are evaluated for their effectiveness in the proposed Hybrid Feder- ated Intrusion Detection System (HybFed IDS).Extensive experiments using real-world IOT datasets such as CICIOT2023 demonstrate the efficacy of these models, achieving high accu- racy and detection rates. The findings highlight the potential of FL-based IDS to offer scalable, resilient, and secure solutions for protecting IoT networks from cyber threats. ---------------------------------------------------------------------------------------- في السنوات الأخيرة، استدعى التوسع السريع لإنترنت الأشياء اتخاذ تدابير أمنية قوية ومتكيّفة لحمايتها من التهديدات السيبرانية المتزايدة التعقيد. تقدم هذه الرسالة تحليلاً شاملاً لأساليب التعلم الموحد للكشف عن التطفل في بيئات إنترنت الأشياء. يركز البحث على تطوير نظام كشف التطفل لامركزي يحافظ على الخصوصية، ويعتمد على أطر التعلم الموحد لتعزيز الأمان دون المساس بخصوصية البيانات. يتم تقييم نماذج التعلم العميق المختلفة، بما في ذلك الشبكات العصبية التلافيفية والشبكات العصبية العميقة وشبكات الذاكرة الطويلة القصيرة المدى، لفعالية نظام الكشف عن التسلل الموحد الهجين المقترح. وتظهر التجارب الموسعة باستخدام مجموعات بيانات إنترنت الأشياء الحقيقية فعالية هذه النماذج، محققة دقة عالية ومعدلات كشف عالية.تبرز النتائج إمكانيات نظام الكشف عن التطفل القائم على التعلم الموحد في تقديم حلول قابلة للتطوير، ومرنة، وآمنة لحماية شبكات إنترنت الأشياء من التهديدات السيبرانية ----------------------------------------------------------------------------------------- Ces dernières années, l’expansion rapide de l’Internet des objets (IoT) a nécessité des solutions robustes. et des mesures de sécurité adaptatives pour se protéger contre les cybermenaces de plus en plus sophistiquées. Cette thèse présente une analyse complète des approches d’apprentissage fédéré (FL) pour détection d’intrusion dans les environnements IoT. L’accent est mis sur le développement d’un système décentralisé de protection de la vie privée. préserver le système de détection d’intrusion (IDS) qui exploite les cadres d’apprentissage fédéré pour améliorez la sécurité sans compromettre la confidentialité des données. Divers modèles d’apprentissage profond, notamment Réseaux de neurones convolutifs (CNN), réseaux de neurones profonds (DNN) et long terme Les réseaux de mémoire (LSTM) sont évalués pour leur efficacité dans la fédération hybride proposée. Système de détection d’intrusion (HybFed IDS). Expériences approfondies utilisant l’IOT du monde réel des ensembles de données tels que CICIOT2023 démontrent l’efficacité de ces modèles, permettant d’obtenir une précision élevée. taux de racée et de détection. Les résultats mettent en évidence le potentiel de l’IDS basé sur FL à offrir des solutions évolutives et des solutions résilientes et sécurisées pour protéger les réseaux IoT contre les cybermenaces.